A recombinant subunit HS aba392 as a potential vaccine for haemorrhagic septicaemia disease in livestock - Rita, D.V.; Swee, K.C.W.; Shamini, C.; Kang, Tzin Lim; Nurshamimi, N.R.; Hussin, A.R.; Ismail, Salmah (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Haemorrhagic septicaemia (HS) is a major disease in cattle and buffaloes, caused by certain serotypes of Pasteurella multocida, mainly B and E serotypes. Frequent HS outbreak has a major impact in many Asian countries, including Malaysia, where farmers encounter economic loss due to low milk production as well as death of their livestock. There are four types of vaccines available; broth bacterins, alum precipitated vaccine, aluminium hydroxide gel vaccine and oil adjuvant vaccine (OAV), but these vaccines can only provide short term immunity and therefore need to be administered annually. Hence, the development of a protein vaccine using recombinant antigen can be a potential candidate for the production of HS vaccine that would give longer immunity. We have successfully cloned the ABA392 gene fragment into a protein expression vector, pET-30a. The protein was expressed from our ABA392/pET30a clone and the immunogenicity of the protein has been tested on rats. This vaccine was able to trigger an immune response and therefore has the potential to be tested as suitable vaccine candidate in future studies. It is envisaged that this subunit vaccine will make a significant contribution in the management of HS among livestock in future.